Avaliação da aprendizagem de alunos surdos no ensino superior: estudo de caso em um curso de graduação em letras libras - Talmag, Ane Frank Araújo (2018)
The theme of learning assessment leads to discussions in educational institutions at their various levels, between educators and researchers, especially with the advent of people with disabilities’ inclusion in the regular system of education. The university must offer conditions for the permanence of these students, with the planning of resources, services, teaching and assessment focused on their specificities, as well as teacher ́s formation for the pedagogic assistance to disabled people. Based on this assumption and considering the lack of studies related to the subject, the main purpose of the current research is to accomplish an investigation about the practice of learning assessment for deaf students registered in a graduate course of Libras in a Public Institute of Higher Education, in Fortaleza-Ceará. Besides, this study specifically aims: i) identifying the accessibility conditions concerning the practices of learning assessment; ii) knowing the difficulties lived by students, professors and coordinators regarding learning assessment for deaf students; iii) gathering contributions of students, professors and coordinators for an inclusive practice of learning assessment. Tyler, Stake, Crombach, Luckesi, Hoffmann and Beyer proposed a theoretical framework in Educational Assessment to this study. Thus, a qualitative research was accomplished and focused on the subjective character of the analyzed object, studying its particularities and individual experiences, as a case study. An intentional sample was composed by: 6 deaf students; 6 professors and 1 graduate level course’s coordinator, 13 subjects altogether. For data collection, semi-structured interviews were conducted and mixed questionnaires were used. The data were analyzed according to Laurence Bardin's Content Analysis. The results revealed that, with an appropriate formation to educate deaf students, an effective assessment of learning aligns with the most recent generations of Educational Evaluation and Inclusive Education. The suggestions obtained pointed to the importance of investing in more technological resources. The difficulties of assessment presented by both students and professors are related to the use of Portuguese as a second language.